FORMULASI SEDIAAN LIP GLOSS DARI BAWANG DAYAK (Eleutherina palmifolia L. Merr) SEBAGAI BAHAN PEWARNA ALAMI KOSMETIK - Euis Setiawati; Ine Suharyani (STIKes Muhammadiyah Kuningan, 2018)
The onions Dayak (Eleutherine palmifolia L. Merr) is the kind of nutritious plants that are empirically for used health. The part that can be used in this plant is tubers whichi has red light and green leaves form of ribbon and flowers are white. The research onions dayak as coloring, to get the color of the isolation of the onions dayak done by the tubers onions dayak still fresh in pieces and bleender, the conducted screening with filter paper that aims to get of red viscous. Previously carried out first optimasi its cera alba three formule its different 3%, 6%, 9%, and formule 3% that generates its efficiency. Formulation was made by using paraffin liquid, vaselin album, emulsyfying wax, butil hidroksi toluen (BHT), nipagin, gliserin, and oleum ricini. The isolation of the onions dayak with three different formulasion 20% rose, 35% red brick, 50% nude. The results of the hedonic test on formule 2 as much as 44% of respondents choose “really like”. While based on the scale numerical and that just formule 2 with a concentration 35% more preferred respondents with the judgment of 76%.